KCC-1/Pr-SO3H: an efficient heterogeneous catalyst for green and one-pot synthesis of 2, 3-dihydroquinazolin-4(1H)-one. Issue 1 (2nd January 2020) - Azizi, Sajjad; Soleymani, Jafar; Hasanzadeh, Mohammad
Abstract: KCC-1/Pr-SO3H is found to be a considerable efficient nanocatalyst for the one-pot three-component condensation coupling of aromatic aldehydes, isatoic anhydride, and primary amines for the synthesis of 2, 3-dihydroquinazolin-4(1H)-ones in ethanol as a green solvent under reflux conditions with excellent yields. The influence of different reaction parameters such as the effects of solvent, temperature, time, and concentration of catalyst for the synthesis of 2, 3-dihydroquinazolin-4(1H)-one (4f) were studied. KCC-1/Pr-SO3H is easily recyclable without the significant loss of catalytic activities after seven times. This mild and simple synthesis method offers some worthwhile advantages including short reaction time, high yield, and convenient work-up procedure. Graphical Abstract: